1
$\begingroup$

I am trying to solve the proof for determining the Fourier series representation of a periodic signal. I understand fourier series equation for Discrete time which is $$x[n] = \sum^{}_{k=<N>} a_k e^{jk\omega_0n}$$ In order to find the Fourier series coefficient we multiply both side by $e^{-jr(2\pi/N)n}$ and summation over N terms, That is: $$\sum^{}_{n=<N>} x[n] e^{-jr(2\pi/N)n} = \sum^{}_{n=<N>} \sum^{}_{k=<N>} a_k e^{j(k-r)(2\pi/N)n}$$

After that i couldn't understand how can we get the final term: $$ a_r = \frac{1}{N} \sum^{}_{n=<N>} x[n]e^{jr(2\pi/N)n}$$

Please, anyone, help me to understand this

$\endgroup$
4
  • $\begingroup$ Does your $\sum_{n=<N>}$ simply mean $\sum_{n=1}^{N}$ ? $\endgroup$
    – Gilles
    Commented Oct 15, 2015 at 21:46
  • $\begingroup$ @Gilles I have no idea about that.. $\endgroup$ Commented Oct 16, 2015 at 3:01
  • $\begingroup$ In the second equation, should the $0$ on top of your summation be there ? $\endgroup$
    – Gilles
    Commented Oct 16, 2015 at 8:13
  • $\begingroup$ No it shouldn't be there... i just changed $\endgroup$ Commented Oct 16, 2015 at 8:57

1 Answer 1

2
$\begingroup$

In the formula displayed for $x[n]$, the exponentials $e^{jk\omega_0 n}$ should be $e^{-jk\omega_0 n}$. I'm assuming that the sum $\sum\limits_{n = \langle N\rangle}$ is extended over all integers $n$ from $0$ to $N-1$. Fix $r\in \{0,\ldots, N-1\}$. Then

$$\sum_{n = \langle N\rangle}x[n]e^{jr\omega_0 n} = \sum_{n = \langle N\rangle}\sum_{k = \langle N\rangle}a_ke^{-jk\omega_0 n}e^{jr\omega_0 n} = \sum_{k = \langle N\rangle} a_k \sum_{n = \langle N\rangle} e^{j(r-k)\omega_0 n}.\tag{*}$$

If $k = r$, then each of the terms $e^{j(r-k)\omega_0 n}$ equals $1$, in which case

$$\sum_{n = \langle N\rangle} e^{j(r-k)\omega_0 n} = N.$$

If $k \neq r$, let $z = e^{j(r-k)\omega_0}$. Then $z\neq 1$ and $z^N = e^{2\pi j(r-k)n} = 1$. Thus

$$\sum_{n = \langle N\rangle} e^{j(r-k)\omega_0 n} = \sum_{n = \langle N\rangle} z^n = \frac{1 - z^N}{1 - z} = 0.$$

In summary,

$$\sum_{n = \langle N\rangle} e^{j(r-k)\omega_0 n} = N\delta_{k,r}.$$

Therefore,

$$\sum_{k = \langle N\rangle} a_k \sum_{n = \langle N\rangle} e^{j(r-k)\omega_0 n} = \sum_{k = \langle N \rangle} a_k (N\delta_{k,r}) = N\sum_{k = \langle N\rangle} a_k \delta_{k,r} = Na_r.\tag{**}$$

Combining (*) and (**),

$$Na_r = \sum_{n = \langle N\rangle} x[n]e^{jr\omega_0 n} = \sum_{n = \langle N\rangle}x[n]e^{jr(2\pi/N)n}.$$

Hence

$$a_r = \frac{1}{N}\sum_{n = \langle N\rangle} x[n]e^{jr(2\pi/N)n}.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.